Tufts yacht club (Tufts College sailing team) - Unknown (Tufts Archival Research Center, 2014)
photographic print. Photograph of the 1939-1940 Tufts Yacht club (Tufts College sailing team). Left to right: John Bielecki, Charles Cosser, Richard kirkpatrick, Phil Varney.